Development of student worksheet based on guided inquiry with class activity and laboratory in thermochemistry material - Kiprah Piawi; Umar Kalmar Nizar; Mawardi Mawardi (Fakultas Ilmu Pendidikan UNP)
The study of development student worksheet based on guided inquiry has been conducted for thermochemistry subject for high school. This study aims to determine the validity, practicality and effectiveness of development student worksheet using plomp model. The results show that the developed student worksheet in very valid categorized (82.1%). The application of guided inquiry in student worksheet has been practicality tested by teachers and students, and it show the result of 81.25% and 85.1%, respectively. This value indicates that student worksheet is very practical. Based on the students activity aspect, the effectiveness student worksheet based on guided inquiry reaches 84.4% (very effective), whereas based on learning outcomes have a n-gain value of 0.6 (medium). It can be concluded that the developed student worksheet is in very valid, very practical and very effective category so as to improve the students understanding.